18‐year follow‐up of enzyme‐replacement therapy in two siblings with attenuated mucopolysaccharidosis I. Issue 2 (5th November 2022) - Pjetraj, Dorina; Santoro, Lucia; Sgattoni, Claudia; Padella, Lucia; Zampini, Lucia; Monachesi, Chiara; Gabrielli, Orazio; Catassi, Carlo
Abstract: Mucopolysaccharidosis type I (MPS I) is an autosomal recessive disorder caused by the deficiency of α‐L‐iduronidase and characterized by a progressive course with multisystem involvement. Clinically, MPS I is divided into two forms: (1) severe (Hurler syndrome), which presents in infancy and is characterized by rapid progressive neurological involvement; (2) attenuated (Hurler/Scheie and Scheie syndromes), which displays a slower progression and absent to mild nervous system involvement. The specific treatment for attenuated MPS I consists of enzyme‐replacement therapy with laronidase (human recombinant α‐L‐iduronidase, Aldurazyme). We present updated data after 18 years of laronidase treatment in two siblings affected by the attenuated form of MPS I who started therapy at 5 months and 5 years of age, respectively. Clinical and laboratory data of the siblings show that long‐term enzyme replacement therapy may improve/stabilize many symptoms already present at the time of the diagnosis and reduce the disease progression. This study confirms that early diagnosis and early initiation of enzyme‐replacement therapy are essential to modify positively the natural history of the attenuated form of MPS I.